Basic management principles of the formation of consumer loyalty to brands of regional companies - E. V. Pisareva; E. S. Sergienko (Управление)
The problem of forming of consumer loyalty to companies that implement market activity in the regions of the Russian Federation on the scale of small and medium business is investigated. Due to the fact that such business structures do not have the opportunity to compete with large international corporations, they should identify their vector of development with a focus on the consumer, understanding that the formation of loyalty is a very important element of ensuring a stable market position. It is noted that the managers need to work towards improving the quality of not only products, but also implemented management measures in a number of areas. The customer satisfaction is an indicator of achieving a match between the subjectively expected value of the product to the potential consumer and the actual value obtained as a result of the experience of its acquisition and consumption. Thus, only in the case of positive consumer experience can the formation of loyal attitude. A list of basic practice-oriented principles that allow to attract customers, to form a loyal attitude to the company and products has been presented. It is determined that the formation of loyalty is not a one-time marketing campaign, but a complex work of a cohesive team of employees under the guidance of an effective manager. Their effective work, implemented on a permanent basis, will ensure the strengthening of the market position of the brand of the regional business structure. The presented principles will help managers working on the scale of small and medium-sized businesses to form and implement their own strategies to ensure the competitiveness of the company and the demand for products in modern turbulent times, which in turn will contribute to a positive impact on the development of the regional economy of our country.